Signal Transduction of hCG Induces Decidualization and Uterine Receptivity - L Bernardini; JP Balmaceda; L Gianaroli; AP Ferraretti; F Rojas; I Moretti-Rojas; JJ Brosens; P Devroey; A Stewart Kaplan (Journal of Fertility Biomarkers, 2017)
All independent experimental data on epithelial and glandular cells lines of human endometrium support the evidence for a rapid production of eicosanoids from the LH/hCG receptors when exposed to the hCG hormone. Prostaglandins rapidly act on the surrounding endometrial stromal cells throughout the adenylyl cyclase enzyme leading to very large amounts of cAMP and angiogenic factors (VEGF) production. The cAMP is the most important intracellular second messenger and along with progesterone accomplishes the full process of decidualization and acquisition of receptivity after estrogenic priming of the endometrium. The status of uterine receptivity lasts few days only and timing for successful embryo-signal transduction system activation by the endometrium is probably short. In absence of in vivo embryonic signals it is impossible to predict, on individual bases, how the intensity of all the complex interlinked molecular changes of decidualization might ever be in case of exposure to native hCG. In other terms, amount of prostaglandins and cAMP produced in response to variably glycosylated hCG are all, in vivo, not measurable variables and should be viewed as a “wave” of biochemical chain reactions. Embryonic hCG is secreted in form of multiple isomers having an unpredictable variable level of glycosylation and control of this variable remains elusive. During cycles of ovarian stimulation many drugs (FSH, LH, HCG) interact with different G-protein coupled receptors (GPCRs) making it possible to alter the prostaglandins-mediated decidualization process ready to be elicited only by hCG of pregnancy. Since the molecules (cAMP and progesterone) controlling endometrial stromal cells differentiation into decidual cells are critical for successful implantation and placenta formation, the evidence of fast eicosanoids production associated with endometrial LH/hCG receptors exposure to hCG and the potential by human endometrium to produce, in response, very large amounts of cAMP has biological and clinical relevance.
Keywords: HCG hormone